33‐1: Invited Paper: TADF based OLED Devices. Issue 1 (29th May 2019) - Yang, Joong-Hwan; Seo, Bo-Min; Hong, Tae-Ryang; Baek, Jeong-Eun; Choi, Hyung-Jong; Noh, Hyo-Jin; Kim, Jun-Yun; Yoon, Dae-Wi; Kim, Chun-Ki; Han, Chang Wook; Choi, Hyun-Chul; Kang, In-Byeong
Abstract : Although TADF has drawn a lot of attention for future high performance OLED, there has rarely been reports on the practical application. Furthermore, many researchers cast a doubt upon device lifetime. In this work, we demonstrated the applicability of TADF into OLED lighting panel. When TADF Blue was employed for 3‐stacked OLED lighting, white OLED (WOLED) showed improvement of power efficiency by about 40%. On the other hand, TADF Green in 2‐stakced WOLED reached the 70% of the device lifetime, compared with WOLED with phosphorescent green.